Water vapour sorption thermodynamic properties and stability of spray dried avocado milkshake powder - Shiby, V K; S, Karthik; T, Priyamvada; Pandey, Mohan chandra (Indian Journal of Dairy Science, 2021)
Abstract Correlation of sorption and glass transition properties were determined for avocado milk shake powder obtained by spray-drying with varying levels (2,6,12%) of maltodextrin (MD). The isotherms were Type III and GAB model was found to be adequate to predict the sorption data. At 25 °C, the critical water content that ensures the glassy state of the shake powder during storage increased from 0.05 to 0.08 g water/g product while the critical water activity increased from 0.14 to nearly 0.6, yield increased and stickiness decreased with increasing levels of MD (2 to 12%) The correlation between Tg and the water fraction present in the sample was fitted using the Gordon–Taylor model showing satisfactory values of R² ( >0.98). From the combined plot of Tg and EMC vs water activity the critical water activity at 20° C is 0.1 which increased to 0.6 at -5°C.